Atherosclerotic Plaque Healing - Vergallo, Rocco; Crea, Filippo (The New England journal of medicine, 2020)
Atherosclerotic plaque rupture and erosion result in acute coronary syndromes. Plaque healing after initial disruption has been less extensively studied. Reviewed are mechanisms and phenotypic features of plaque healing, its role in clinical events, and therapeutic implications.